Harmonisasi Marpege-Pege dan Hadis Nabi: Studi Living Hadis di Desa Pargarutan Kabupaten Tapanuli Selatan Sumatera Utara - Efendi, Rustam; Damanik, Nurliana (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
The Marpege-Pege tradition, a practice of mutual assistance and cooperation in the Pargarutan Village community, South Tapanuli Regency, is a form of local wisdom that still survives amidst the currents of modernization. This research is based on the academic urgency to show how living hadith works within the local cultural realm and contributes to the preservation of customary values that are in harmony with Islam. The research aims to identify Marpege-Pege values that are relevant to Islamic principles, interpret their relationship with the hadith on mutual assistance, brotherhood, and deliberation, and explain the internalization of hadith teachings in the community's social practices. This research was conducted using a qualitative-phenomenological method with participatory observation, in-depth interviews, and field documentation as primary data sources, which were then analyzed by emphasizing the relationship between the hadith text and customary practices. The results show that Marpege-Pege is understood by the community not only as a customary tradition, but also as an implementation of the Prophet's hadith on community solidarity, mutual cooperation in goodness, and mutual assistance in social and religious matters. Collective activities such as housebuilding, weddings, and agricultural management demonstrate the values of togetherness, deliberation, volunteerism, and Islamic brotherhood, which serve as the basis for religious legitimacy for these practices. In conclusion, Marpege-Pege serves as a medium for harmonious integration between custom and Islam, while demonstrating the relevance of living hadith in strengthening social cohesion and providing a conceptual contribution to the study of the relationship between local traditions and Islamic teachings.